Transport Properties in Chemically Doped Metallic Nanotubes (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied the transport properties in periodic chemically nitrogen doped  metallic nanotubes. We have found that the ballistic properties of carbon nanotubes  remained for some doping configurations. It was also found that the resonant effect  associated with specific symmetry of the wave function was close to the Fermilevel.  We have shown that both axial and screw periodicities gave rise to such a behavior  and that specific but realistic disorder preserved this ballistic transport in doped  metallic carbon nanotube. The properties which were four found during  investigation are related to long range correlation effects predicted for the electronic  properties and the quantum transport of nitrogen doped graphene when chemical  dopic effects only one of the two sublattices of graphene. For the purpose of  research paper we have used Green’s formalism in the framework of the tight  binding approach. We have found that conductance response was unchanged  because one of the two conductance channels remained open for symmetry reasons.  It was also found that the energy of the quasibound states depend on the specific  local modification but not based on the symmetry of the quasibound states. The  bound properties remained true for both armchair and chiral nanotubes. The  obtained results were in good agreement with previously obtained results.